(untitled) (Proceedings of International Educators Conference, 2024)
At the end of the XX-XXI century, the world community faced not only a medical, but also a global problem of great socio-economic importance - a pandemic of chronic diseases. As a result of such changes, a number of changes have also begun to occur in the psyche of people due to social and economic difficulties. The defecation observed in schizophrenia is not particularly pronounced in patients with exactly the same diagnosis for several years.